Wireless power transfer for mobile robot with capacity optimization and dynamic protection considerations. (17th February 2023) - Lee, Tsong-Shing; Hung, Te-Chun; Huang, Kuan-Chieh
ABSTRACT: In this paper, a wireless charging system that can perform coil capacity optimization and dynamic protection is proposed for mobile robots. Poor wireless charging performance might be obtained because of the inability to achieve reliable capacity estimation and effective charging detection; therefore, in this study, suitable solutions were identified for capacity estimation and effective charging detection. First, resonance analysis was conducted on a systematic flexible coil design to maximize its charging capacity. Second, a dynamic protection mechanism was developed to handle unexpected charging mistakes caused by misalignment. Third, a pickup terminal feedback system integrated with a Bluetooth chip and microprocessor unit was embedded to maintain the requisite output voltage. This system was validated through simulations and hardware implementations. The experimental results indicate that a setup based on the proposed design delivers a power of 3.2 kW at an efficiency of 91.4%, which confirms the efficacy and feasibility of the proposed approach for robot charging.